2020
DOI: 10.1002/prop.202000069
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Transitions Between Minkowski and de Sitter Spacetimes

Abstract: Quantum transitions among de Sitter and Minkowski spacetimes through bubble nucleation are revisited using the Hamiltonian formalism. We interpret tunnelling probabilities as relative probabilities: the ratio of the squared wave functionals P=false|normalΨscriptNfalse|2false|normalΨscriptBfalse|2, with ΨscriptB,scriptN solutions of the Wheeler‐DeWitt equation corresponding to the spacetimes scriptN and scriptB, gives the probability of nucleating the state scriptN relative to the probability of having the stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…In previous studies [7,18,22], the tunneling transition rates from Minkowski and AdS universes to dS universes are assumed to be zero. Recent studies show that there is a possibility of the tunneling transition from Minkowski or AdS vacuum to dS universes through the bounce [8][9][10][11][12][13][14][15]. In [15], the authors showed that if we choose suitable boundary conditions, the detailed balance can be broken down.…”
Section: The Probabilistic Evolution Of Multiverse Dictated By the Mamentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies [7,18,22], the tunneling transition rates from Minkowski and AdS universes to dS universes are assumed to be zero. Recent studies show that there is a possibility of the tunneling transition from Minkowski or AdS vacuum to dS universes through the bounce [8][9][10][11][12][13][14][15]. In [15], the authors showed that if we choose suitable boundary conditions, the detailed balance can be broken down.…”
Section: The Probabilistic Evolution Of Multiverse Dictated By the Mamentioning
confidence: 99%
“…S 1,2,3,4 are certain small constants. Noted that although equation (219) appears to be a numerical setting, it contains the main point that the tunneling may occur from Minkowski (or AdS) universes to dS universes which can break down the detail balance [15] under proper boundary conditions. This feature is captured in the currernt work.…”
Section: The Probabilistic Evolution Of Multiverse Dictated By the Mamentioning
confidence: 99%
See 2 more Smart Citations
“…In presence of the Z 2 -symmetry breaking our setup contains a whole set of nondegenerate local minima with vacuum energy splitting of order V 0 δ 2 whose vacuum energy increases with increasing φ 1 -distance from the set of global minima at (φ 1 = 0, φ 2 = 2πn/c). Between the local minima of this mini-landscape there will be tunnelling instanton transitions described by Coleman and de Luccia (CdL) [57] (for very recent work re-analyzing CdL tunnelling using the Hamiltonian-Wheeler-DeWitt approach, see [58]).…”
Section: Jhep12(2020)161mentioning
confidence: 99%